Malaysia travel destination images search engine using Geometric Moment Invariants - Ali, Selamat; Teh, Jian Ting (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.